Challenges Faced by Nursing Faculty in Curriculum Implementation in Nursing Schools of Sindh: Nurses Faculty Perspectives - Sodho, Mahaveer Singh; Fatima, Musarat; Abbas , Zeeshan (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To identify the challenges faced by the nursing faculty in the implementation of the curriculum in nursing schools in the public sector in Sindh province. Methodology: This analytic cross-sectional study from October – December 2019 was carried out at Public sector nursing schools including Schools of Nursing at Karachi, Hyderabad, Thatta, Badin, Mirpurkhas, Sanghar, Shaheed Benazir Abad, Khairpur, Sukkur, Shikarpur, Larkana, and Jacobabad which are offering diploma program in the interior southern region of Sindh were chosen. Nonprobability convenience sampling using Raosoft software was used. Total 123 participants were selected. All the nursing faculty both male and female who consented to be part of the study having at least one year of experience of work in public nursing school and qualifying either PGD/BSc.N(Post R.N)/BSc.N/MPH/MSPH/MSc.N. The data was entered and analyzed using a statistical package (freq) for social science (SPSS) version 23.0. Results: The majority of respondents were females (64.2%), while most of the respondents were clinical instructors (55%). Challenges like resources were found severely, whereas personal challenges were found on a moderate level. Highlighted issues identified were lack of training sessions (66.7%), non-availability of computer lab (70%), communication gaps (61.7%), poor interest by faculty in the implementation of curriculum (50.8%), irregular facilitation of teaching gadgets (56.7%) were found most significantly association (p = 0.000). Conclusion: There was an Existence of Challenges among faculty that should be eradicated to ensure a productive outcome through effective implantation by faculty. This will surely develop a productive result for society depends over heath sector. Keywords: Curriculum, Nursing Faculty, Challenge, Schools, Perspective.